An AWARENESS OF DELAYED HEALING IN POST-OPERATIVE FRACTURE CONDITIONS IN OSTEOPOROTIC PATIENTS - VIJU, KEZIAH K; SHAH, MAYURI R (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The study aimed to determine the knowledge of delayed healing in postoperative fracture conditions in osteoporotic patients. Method: In this observational study, 60 subjects were taken between the age group 50–80 years, which consisted of 52% of females and 48% of males. The study was done with self-made questionnaires. Result: A sample of 60 people was taken; out of this, only 11% were aware of the relationship between osteoporosis and fracture healing, and the other 89% lacked the awareness of the relationship between osteoporosis and fracture healing. Conclusion: In this study, it was found that there was 11% of people aware of fracture healing and osteoporosis.